Pressure dependence of the silicon carbide synthesis temperature - Limandri, Silvina Paola (2019)
The starting temperature for SiC synthesis from elemental silicon, carbon black, and graphite powders was determined for pressures ranging from 0.8 to 11 GPa by in situ X-ray diffraction experiments. The synthesized SiC corresponds to the cubic 3C phase with the presence of stacking faults along the [111] direction. The lowest density of the stacking faults is achieved when black carbon is used instead of graphite. The minimum temperature to start the Si + C → SiC reaction slightly decreases when the pressure is increased up to 6 GPa and the reaction begins before silicon melts. For pressures higher than 8 GPa, the starting temperature increases, and the formation of SiC from the SiII phase requires the complete melting of silicon. Bulk modulus Bo= 236(14) GPa was obtained for the synthesized SiC phase.